Provenance of the Gamburtsev Subglacial Mountains from U-Pb and Hf analysis of detrital zircons in Cretaceous to Quaternary sediments in Prydz Bay and beneath the Amery Ice Shelf - Veevers, J. J.; Saeed, Ayesha; O'Brien, P. E. (Sedimentary Geology, 2008)
In central Antarctica, drainage today and earlier back to the Paleozoic radiates from the Gamburtsev Subglacial Mountains (GSM). Proximal to the GSM past the Permian-Triassic fluvial sandstones in the Prince Charles Mountains (PCM) are Cretaceous, Eocene, and Pleistocene sediment in Prydz Bay (ODP741,1166, and 1167) and pre-Holocene sediment in AM04 beneath the Amery Ice Shelf. We analysed detrital zircons for U-Pb ages, Hf-isotope compositions, and trace elements to determine the age, rock type, source of the host magma, and "crustal" model age (T-DM(C)). These samples, together with others downslope from the GSM and the Vostok Subglacial Highlands (VSH), define major clusters of detrital zircons interpreted as coming from (1) 700 to 460 Ma mafic granitoids and alkaline rock, epsilon Hf 9 to -28, signifying derivation 2.5 to 1.3 Ga from fertile and recycled crust, and (2) 1200-900 Ma mafic granitoids and alkaline rock, epsilon Hf 11 to -28, signify inderivation 1.8 to 1.3 Ga from fertile and recycled crust. Minor clusters extend to 3350 Ma. Similar detrital zircons in Permian-Triassic, Ordovician, Cambrian, and Neoproterozoic sandstones located along the PaleoPacific margin of East Antarctica and southeast Australia further downslope from central Antarctica reflect the upslope GSM-VSH nucleus of the central Antarctic provenance as a complex of 1200-900 Ma (Grenville) mafic granitoids and alkaline rocks and older rocks embedded in 700-460 Ma (Pan-Gondwanaland) fold belts. The wider central Antarctic provenance (CAP) is tentatively divided into a central sector with negative epsilon Hf in its 1200-900 Ma rocks bounded on either side by positive epsilon Hf. The high ground of the GSM-VSH in the Permian and later to the present day is attributed to crustal shortening by far-field stress during the 320 Ma mid-Carboniferous collision of Gondwanaland and Laurussia. Earlier uplifts in the similar to 500 Ma Cambrian possibly followed the 700-500 Ma assembly of Gondwanaland, and in the Neoproterozoic the 1000-900 Ma ...